Exploring the Challenges and Opportunities Faced by Women Entrepreneurs in Sukabumi District: A Qualitative Study - Feb Amni Hayati; Rani Eka Arini (West Science Interdisciplinary Studies, 2023)
This qualitative study explores the challenges and opportunities women entrepreneurs face in Sukabumi District, Indonesia. The study involved 15 women entrepreneurs who were selected using a purposeful sample. Data was collected through in-depth interviews, focus group discussions, and observations. The study found that women entrepreneurs face various challenges, including limited access to financial resources, Lack of business skills, social stereotypes, and gender-based discrimination. However, the study also reveals that women entrepreneurs are a formidable resource and have ways to overcome those challenges by networking, acquiring new skills, and leveraging their social capital. The study suggests policies and programs that address women entrepreneurs' specific challenges and provide the support needed to grow and succeed.